Chronotherapeutic effect of orexin antagonists on glucose metabolism in diabetic mice. Issue 1 (October 2019) - Kon, Kanta; Tsuneki, Hiroshi; Ito, Hisakatsu; Takemura, Yoshinori; Sato, Kiyofumi; Yamazaki, Mitsuaki; Ishii, Yoko; Sasahara, Masakiyo; Rudich, Assaf; Maeda, Takahiro; Wada, Tsutomu; Sasaoka, Toshiyasu
Abstract : Disrupted sleep is associated with increased risk of type 2 diabetes. Central actions of orexin, mediated by orexin-1 and orexin-2 receptors, play a crucial role in the maintenance of wakefulness; accordingly, excessive activation of the orexin system causes insomnia. Resting-phase administration of dual orexin receptor antagonist (DORA) has been shown to improve sleep abnormalities and glucose intolerance in type 2 diabetic db/db mice, although the mechanism remains unknown. In the present study, to investigate the presence of functional link between sleep and glucose metabolism, the influences of orexin antagonists with or without sleep-promoting effects were compared on glucose metabolism in diabetic mice. In db/db mice, 2-SORA-MK1064 (an orexin-2 receptor antagonist) and DORA-12 (a DORA) acutely improved non-rapid eye movement sleep, whereas 1-SORA-1 (an orexin-1 receptor antagonist) had no effect. Chronic resting-phase administration of these drugs improved glucose intolerance, without affecting body weight, food intake, locomotor activity and energy expenditure calculated from O2 consumption and CO2 production. The expression levels of proinflammatory factors in the liver were reduced by 2-SORA-MK1064 and DORA-12, but not 1-SORA-1, whereas those in the white adipose tissue were reduced by 1-SORA-1 and DORA-12 more efficiently than 2-SORA-MK1064. When administered chronically at awake phase, these drugs caused no effect. In streptozotocin-induced type 1-like diabetic mice, neither abnormality in sleep–wake behavior nor improvement of glucose intolerance by these drugs were observed. These results suggest that both 1-SORA-type (sleep-independent) and 2-SORA-type (possibly sleep-dependent) mechanisms can provide chronotherapeutic effects against type 2 diabetes associated with sleep disturbances in db/db mice.